Attenuated Bacteria as Immunotherapeutic Tools for Cancer Treatment - Kaimala, Suneesh; Al-Sbiei, Ashraf; Cabral-Marques, Otavio; Fernandez-Cabezudo, Maria J.; Al-Ramadi, Basel K. (Frontiers in Oncology, 2018)
The use of attenuated bacteria as cancer therapeutic tools has garnered increasing scientific interest over the past 10 years. This is largely due to the development of bacterial strains that maintain good anti-tumor efficacy but with reduced potential to cause toxicities to the host. Because of its ability to replicate in viable as well as necrotic tissue, cancer therapy using attenuated strains of facultative anaerobic bacteria, such as Salmonella, has several advantages over standard treatment modalities, including chemotherapy and radiotherapy. Despite some findings suggesting that it may operate through a direct cytotoxic effect against cancer cells, there is accumulating evidence demonstrating that bacterial therapy acts by modulating cells of the immune system to counter the growth of the tumor. Herein, we review the experimental evidence underlying the success of bacterial immunotherapy against cancer and highlight the cellular and molecular alterations in the peripheral immune system and within the tumor microenvironment that have been reported following different forms of bacterial therapy. Our improved understanding of these mechanisms should greatly aid in the translational application of bacterial therapy to cancer patients.